Philosophical Examination of the Itsbat Nikah (Marriage Legalization) in Sirri Polygamy Following the Issuance of Supreme Court Circular No. 3 of 2018 - Adriyeni, Adriyeni Adriyeni; Wahyuni, Zikra; Daipon, Dahyul (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Supreme Court Circular (SEMA) No. 3 of 2018 has effectively eliminated the possibility of granting requests for marriage registration in cases of polygamous marriages based on unregistered unions. This provision raises concerns about its potential to create various problems, particularly in relation to the protection of women and children. This research aims to analyze the issues arising in marriage law following the issuance of SEMA No. 3 of 2018 and its relevance to the protection of women and children, as well as the regulation of itsbat nikah (marriage legalization) for sirri polygamous marriages from the perspective of maqashid sharia. The study employs a library research methodology, utilizing secondary data sources. The data were collected through literature reviews and analyzed using qualitative data analysis methods. The findings indicate that the regulation of itsbat nikah for sirri polygamous marriages under SEMA No. 3 of 2018 aligns with the principles of protecting women and children. This regulation was introduced to uphold the core values enshrined in Indonesia’s marriage laws. From the perspective of maqashid sharia, the provisions in SEMA No. 3 of 2018 correspond to the objectives of maqashid in preserving maslahah (public interest) at the dharuriyat level, particularly in safeguarding religion, lineage, and property.